2014
DOI: 10.5897/ajmr2014.6607
|View full text |Cite
|
Sign up to set email alerts
|

Different cover promote sandy soil suppressiveness to root rot disease of cassava caused by Fusarium solani

Abstract: Sandy soils of 19 arable fields were analyzed for disease suppressiveness against root rot disease of cassava, caused by Fusarium solani CFF109. Analysis of chemical, physical, biochemical, microbial population and activity, and soil characteristics were assessed. Soils with different management histories and covers most commonly found in the region were collected to build a greenhouse experiment, to evaluate the natural suppressiveness of soils against cassava root rot. The severity was submitted with all dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…The maize crop showed a higher rate of disease and colonization by pathogens on the cuttings, it is worth mentioning that maize cultivation is frequent in monoculture, generating an increase in the incidence of pathogen populations, and in the present study this situation was confirmed, corroborating the results found by Awoyemi et al, (2016) in which the intercropping of maize with cassava does not have management potential in the development of root rot. However, it differs from what was found by Barros et al, (2014) andDe Medeiros et al, (2019) who presented it as one of the possible plant covers that can influence soil suppression when intercropped with beans and cassava; however, the planting of this plant was for a long period, unlike what happened in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The maize crop showed a higher rate of disease and colonization by pathogens on the cuttings, it is worth mentioning that maize cultivation is frequent in monoculture, generating an increase in the incidence of pathogen populations, and in the present study this situation was confirmed, corroborating the results found by Awoyemi et al, (2016) in which the intercropping of maize with cassava does not have management potential in the development of root rot. However, it differs from what was found by Barros et al, (2014) andDe Medeiros et al, (2019) who presented it as one of the possible plant covers that can influence soil suppression when intercropped with beans and cassava; however, the planting of this plant was for a long period, unlike what happened in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Alternatively, the induction of suppressiveness is a promising strategy, given the positive results obtained in recent literature (Barros et al, 2014;Silva et al, 2017;De Medeiros et al, 2019). This suppressiveness of the soil consists of limiting the disease, because despite adequate conditions such as a susceptible plant, virulent pathogen and an environment that favors the development of the disease, the disease may not occur, but if it does, it would be less severe (Bettiol and Ghini 2005;Kinkel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…solani is a harmful fungus that causes plant diseases and then affects plant growth and production. The cassava root rot has been responsible for major losses in cassava production, which is mainly caused by the fungi F. solani ( Barros et al, 2014 ; Boas et al, 2016 ). In contrast, the proportions of Chaetomium and Penicillium were gradually increased after CF application, which are beneficial fungi with biocontrol effect on many plant pathogens ( De Cal et al, 2008 ; Shanthiyaa et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diseases incited by soil-borne pathogens are a serious problem for agriculture due to the complexity of their interaction with the environment, difficult management and control 8 . Different management strategies have been reported for CRRD such as crop rotation, chemical control, soil disinfestation by water vapor, soil solarization, alternative controls by plant extracts and oils, and use of biological control agents 7 , 9 12 . However, the use of genetic resistance is considered the less expensive and most environmentally friendly method for cassava root rot disease management in the long term 13 – 16 .…”
Section: Introductionmentioning
confidence: 99%